The first term of a sequence is 3 and each after the first is 2 more than the previous term. What is the expression for the nth term of the sequence for any positive integer n? 

3 Answers | Add Yours

gsenviro's profile pic

gsenviro | College Teacher | (Level 1) Educator Emeritus

Posted on

Using the given data, the first term is 3 and the subsequent terms are 5,7,9,11,....

So the series is: 3,5,7,9,11,13,15,.......

Here `P_1` = 3

and each subsequent term differs by 2, 

i.e., `P_2 - P_1 = 2`

or, `P_2 = P_1 +2`  

similarly, `P_3 = P_2 + 2 = P_1 + 2*2 = P_1 + 2*(3-1)`

and so on,

thus, the nth term of the series is given by,

`P_n = 3+ 2*(n-1)`

this can also be written as

`P_n = 2n +1`

We can verify the answer by choosing any value of n

say, n=1, P1 = 2(1)+1 = 3

n=3, P3 = 2(3)+1 = 7...and so on.

Hope this helps.

bababeta's profile pic

bababeta | Middle School Teacher | (Level 1) Adjunct Educator

Posted on

The sequence would be like this

3,5,7,9,.....

The formula for finding the nth term is an = a +(n-1)d

So here first term(a) is 3 and difference (d) is constant between terms which is (5-3)=2 

So nth term of this sequence is

an = 3 +(n-1)2

  =3 +2n-2

=2n+1

Educator Approved

Educator Approved
kspcr111's profile picture

kspcr111 | In Training Educator

Posted on

As per the data given the first term of the sequence is

a = 3 with a common difference d = 2

so,

The sequence is as follows

3,5,7,9...........`n^(th)` term

Now we have to find the `n^(th) ` term 

The above sequence is an arithmetic progression where common difference (d) = 2

and a = 3

In general, the nth term of an arithmetic progression, with first term a and common difference d, is:

nth term = `a + (n - 1)d`

              = `3+ (n-1)*(2)`

              = `3+2*n -2`

              = `2*n +1`

is the nth term 

:)

              

Sources:

We’ve answered 318,988 questions. We can answer yours, too.

Ask a question